Differential Diagnosis of Central Neurocytoma: Two Cases - Steinsiepe, V.K; Frick, H; Jochum, W; Fournier, J.Y (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Central neurocytoma are rare primary brain tumors of the young and middle-aged adult, typically located in the lateral ventricles. Diagnosis has historically been difficult due to histomorphologic similarities to oligodendroglioma and ependymal tumors and remains a challenge even today. We present two cases of intraventricular central neurocytoma in which careful consideration of the clinical and radiological findings led to reevaluation of the preliminary histological interpretation, highlighting the importance of a meticulous differential diagnosis.
Keywords: neurocytoma; cerebral ventricle neoplasm; differential diagnosis; case report; immunohistochemistry